To What Extent Must, and Can, the Boards of Norwegian Limited Liability Companies and Public Limited Liability Companies Consider Sustainability? - Tore Bråthen; Stine Winger Minde (Oslo Law Review)
The article discusses the Norwegian judicial framework for the work by boards of limited liability companies with sustainability. Sustainability regulation is no longer a result of more or less targeted political initiatives, it largely presents as a coherent system of rules and it has in many ways indisputably been integrated into the field of company law in Norway. The starting point for the analysis is that the boards of Norwegian limited liability companies and public limited liability companies are expected to create value for their owners, but they are also expected to do this in a sustainable manner. Therefore, we firstly give a description of the ‘company interestʼ and its central elements. The article seeks among other things to demonstrate the trade-off between profit seeking and the boardʼs right and duty to integrate sustainability in the management of the company. The boardʼs work on sustainability in limited liability companies and public limited liability companies must be carried out within the framework stipulated by company law and other legislation, the companyʼs articles of association, and the companyʼs other governing bodies. Neither the Limited Liability Companies Act nor the Public Limited Liability Companies Act includes any specific statutory regulation of sustainability. A starting point is, therefore, that the company law framework for the boardʼs work on sustainability is constituted by the general rules in the Companies Acts on the boardʼs right and duty to manage the company in accordance with the company interest. Norwegian company law is stakeholder-oriented and takes into account both shareholder interests and stakeholder interests. Company interest includes the interests of shareholders, employees, counterparties, creditors and society as a whole. As pointed out in the article, these interests include what can be described as ‘sustainability considerationsʼ. The boards of limited liability companies and public limited liability companies must exercise their management of the company within the statutory framework. This framework also includes mandatory legislation other than the Companies Acts, for example the legislation dealing with sustainability matters. For public limited companies listed on the stock exchange, the Norwegian Code of Practice for Corporate Governance includes a specific expectation that the board must integrate sustainability into its governance of the companyʼs business activities. Another important question is to what extent the board can attach importance to sustainability considerations. It is a prerequisite for companies to be able to consider environmental and social considerations that they are financially sustainable. However, it is conceivable that the profit motive can come into conflict with social and environmental considerations. The article discusses the balance between the profit motive and social and environmental considerations. One question deals with the boardʼs ability to attach weight to sustainability in the light of the companyʼs advertising and reputation values (‘goodwillʼ). The article discusses also the relationship between sustainability and the companyʼs ability to make gifts.